Hubungan Psychological Well Being dengan Hipertensi Pada Lansia Penderita Hipertensi di Wilayah Kerja Puskesmas Gugak Panjang - Izzati, Wisnatul; Damaiyanti, Siska; Irwan, Ersha Meita (Jurnal Ners, 2024)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. One of the factors causing hypertension can be a person's psychological condition. Psychological problems such as stress and unstable emotions. Stress and unstable emotional states can have an effect on high blood pressure because they affect the immune system. Psychological well being is the state of a person who has positive behavior towards himself and others, is able to control the environment, and has a goal in life. A preliminary study carried out at the Guguak Panjang Community Health Center found that the number of elderly people suffering from hypertension was 172 people. The aim of the research is to find out "Relationship Psychological Well Being With Hypertension in Elderly People Suffering from Hypertension in the Guguak Panjang Community Health Center Work Area in 2023”. This type of research is correlational descriptive with the approach method cross sectional. The population of this study was 172 elderly people with hypertension in the Guguak Panjang Community Health Center working area. The sample in this study was 172 respondents, using sampling technique total sampling. Data collection psychological well being using a questionnaire scale of psychological well being and hypertension using blood pressure measurements, with univariate and bivariate analysis using SPSS using tests spearmen’s rank. The research results show that the level psychological well being namely low frequency, 112 respondents (65,1%), elderly hypertension, namely grade 1 hypertension was 97 respondents (56,4%). The conclusion of the analysis results shows that there is a significant relationship between psychological well being with hypertension in the elderly with a PValue 0.000 < 0.005. It is recommended for hypertension sufferers to increase it pscholigical well being so that he can control his hypertension. Keywords: Psychological Well Being, Hypertension, Elderly